ANALISIS DAYA DUKUNG PONDASI TIANG PANCANG PADA PEMBANGUNAN ASRAMA PUTRI MTA KARANGANYAR - Fajar, Maulana; Arbianto, Reki; Amhudo, Rasyiid Lathiif (Journal of Civil Engineering and Infrastructure Technology, 2025)
This study analyses the bearing capacity of pile foundations in the construction project of the MTA Women's Boarding School Dormitory in Karanganyar Regency, Central Java. Pile foundations were chosen due to unstable soil conditions and the need for structures capable of withstanding large loads. This study combines analytical approach based on Cone Penetration Test (CPT) data with numerical simulation using Geo5 PILEGROUP software to evaluate the axial, lateral and settlement bearing capacity of the foundation. CPT data was taken from three points (S1, S2, S3) with an investigation depth of up to 13 metres. Single pile bearing capacity analyses were conducted using the Mayerhof (1976) method for axial loads and the Broms (1964) method for lateral loads. The results of the calculation obtained the largest value of S1 sondir D30 Qa = 40 tonnes, D40 Qa = 68 tonnes, and D60 = 147 tonnes. group pile analysis was carried out by considering group efficiency, distance between poles, and load distribution. The results showed that the 2-pile configuration with 3D spacing (1.8 m) was able to withstand a maximum load of 2398.135 kN, greater than the largest structural load (1582.305 kN). The pile group efficiency ranged from 0.998-1, indicating high effectiveness in distributing loads. Foundation settlement was calculated using the semi-empirical method, with the results of the largest single pile settlement of 0.6m diameter Sg = 0.022 m and pile group Sg = 0.043 m in S2 sondir data. and in geo5 software the largest settlement at D40 = 4.3 cm.